Internationalisation at Stellenbosch University during the international academic boycott of the apartheid era (1948–1994). (2nd January 2016) - Baumert, Stefanie; Botha, Jan
ABSTRACT: In this article, we address the international dimension of Stellenbosch University (SU) during the apartheid era, most notably during the academic boycott of South African universities between the early 1960s and the early 1990s. Based on information gathered from the documentary sources of the university and interviews with key role players at the university, the findings of the research will put some of the well-established hypotheses on South Africa's academic isolation and an increasing localism in higher education during that period into perspective. The article will show that prior to 1990 there were different kinds of international activities going on at SU, despite the academic boycotts.